2016
DOI: 10.1186/s11658-016-0003-3
|View full text |Cite
|
Sign up to set email alerts
|

WNT5A–ROR2 is induced by inflammatory mediators and is involved in the migration of human ovarian cancer cell line SKOV-3

Abstract: BackgroundWnt5A, which is a member of the non-transforming Wnt protein family, is implicated in inflammatory processes. It is also highly expressed by ovarian cancer cells. ROR2, which is a member of the Ror-family of receptor tyrosine kinases, acts as a receptor or co-receptor for Wnt5A. The Wnt5A–ROR2 signaling pathway plays essential roles in the migration and invasion of several types of tumor cell and influences their cell polarity. We investigated the modulation of Wnt5A–ROR2 by inflammatory mediators an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…WNT/PCP or WNT5A/ROR/Frizzled signaling promotes invasion, survival and therapeutic resistance of human cancers ( 135 141 ), although WNT5A or non-canonical WNT/Ca 2+ signaling is context-dependently involved in tumor suppression ( 142 144 ). ROR1 is preferentially upregulated in B-cell leukemia, such as chronic lymphocytic leukemia (CLL) ( 145 ) and t(1;19) acute lymphoblastic leukemia (ALL) ( 146 ).…”
Section: Human Diseases Related To Core Pcp Componentsmentioning
confidence: 99%
“…WNT/PCP or WNT5A/ROR/Frizzled signaling promotes invasion, survival and therapeutic resistance of human cancers ( 135 141 ), although WNT5A or non-canonical WNT/Ca 2+ signaling is context-dependently involved in tumor suppression ( 142 144 ). ROR1 is preferentially upregulated in B-cell leukemia, such as chronic lymphocytic leukemia (CLL) ( 145 ) and t(1;19) acute lymphoblastic leukemia (ALL) ( 146 ).…”
Section: Human Diseases Related To Core Pcp Componentsmentioning
confidence: 99%
“…We revealed that during the activation of the NF-κB pathway, miR-429 reduced the level of activated NF-κB by suppressing IKKβ. It has been reported that many other signaling pathways are also involved in tumor migration and other processes, such as the Wnt signaling pathway [33,34]. Whether there are other signaling pathways involved in neuroblastoma is a question worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…ROR2 is recently emerging as a new target for anti-cancer therapeutic intervention, owing to its expression in several cancers, in which it strongly correlates with more aggressive disease states (Debebe & Rathmell, 2015;Yang et al, 2017). Moreover, in some cancer models, ROR2 has been demonstrated to be involved in migration, invasion, (Arabzadeh, Hossein, Salehi-Dulabi, & Zarnani, 2016;Henry, Llamosas, Djordjevic, Hacker, & Ford, 2016) and metastasis (Lai et al, 2012). Nevertheless, the expression and function of ROR2 have never been investigated in MM and deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%